Effects of 3-Benzoyl-7-Hydroxy Coumarin Compound on TNF-? and Caspase-3 Immunreactivity in Kidneys of Rats Exposed to Aluminum - Turk, Ahmet; Kuloğlu, Tuncay; Zencirci, Busra; Gurel, Ali; Karadag, Abdullah; Ozay, Yusuf; Ozkaya, Ahmet (ABADER (Adıyaman Bilimsel Arastırmalar Dernegi), 2023)
This study aimed to investigate the effects of 3-benzoyl-7-hydroxy coumarin compound on apoptotic markers in the kidney tissues of rats treated with Aluminum (Alu). 28 Wistar albino male rats were divided into four groups (n = 7) as: Control Group: 1 ml/kg 0.9% NaCl was administered by oral gavage every other day during the experiment. Aluminium (Alu) Group: Alu was prepared in water and given intraperitoneally (i.p) for 30 days at an excess of 8.3 mg/kg/day. Treatment Group: 10 mg/kg 3-Benzoyl-7-Hydroxy Coumarin was administered to rats by oral gavage every other day for 30 days. Alu + Treatment Group: 8.3 mg/kg Alu was prepared in water and administered i.p for 30 days every other day, and then 10 mg/kg 3-Benzoyl-7-Hydroxy Coumarin was administered to rats by oral gavage every other day for 30 days. At the end of the 30-day experiment, the kidney tissue of the animals was removed under anesthesia and stored under appropriate conditions. In according to our data, Alu administration caused increased Caspase-3 TNF-? and MDA levels in the kidney tissue and 3-benzoyl-7-hydroxy coumarin was found to reverse these changes significantly. © 2023, ABADER (Adıyaman Bilimsel Arastırmalar Dernegi). All rights reserved.
Alüminyuma Maruz Kalan Sıçanların Böbreklerinde 3-Benzoil-7-Hidroksi Kumarin Bileşiğinin TNF-? ve Kaspaz-3 İmmün Reaktivitesi Üzerine Etkileri
Keywords: Apoptosis; Immunohistochemistry; Oxidative stress; Proinflamatuar cytokine